Impactos físico-químicos da disposição de rejeito de dessalinizadores das águas de poços em solos do Oeste Potiguar - Oliveira, André Moreira de (Universidade Federal Rural do Semi-Árido, 2016)
In spite of the fact that crystalline basement predominates with brackish water wells in Brazilian thirstland, desalination technology by reverse osmosis enables its potabilization. Since the late nineties, reverse osmosis desalination devices have been deployed in order to meet the water demand for human consumption, especially in the rural Northeast. Nevertheless, difficulties are present in such deployment like lack of operation and proper maintenance, causing stoppage thereof and producing high-level reject brine, which is usually discharged to the ground without any criteria, and its main consequence has been soil salinity increase over time. Thus, this works aims at evaluating the outcome of the reverse osmosis desalination discharge and its influence in physicochemical attributes of distinct receiver soils in rural communities from Potiguar west. This research was conducted between 2013 and 2014. At first, the communities which were supplied by catchment and treatment of desalinated water centers were registered through a cadastral survey. In order to do so, four data collection expeditions took place in different periods, raining season and drought, on the soils receiving reject brine. Three distances were used (0, 1 and 2 meters from the discharge points) with two layers for each point (0-20cm and 20-40 cm) as well as the evaluation of a) the reverse osmosis treated water quality, b) the well, c) the reject brine. Physicochemical attributes of water for irrigation was also analyzed as well as soil samples for a fertility evaluation. Data were subjected to statistical average tests by Scott Knott to verify the behavior within the points and layers according to each period and between all four periods. The waters were classified according to its use for irrigation; leakage risks and toxicity in plants. The soils were classified according to salinity, Ph considering CE and PST. In the monitored rural communities, the reversed osmosis water treatment stations produce desalinated water with low concentrations of salts, with 68% of all samples are in C1S1 rating class; 25% in C2S1 and class; only 7% in C3S1 class. Regarding the reject brine, 93% of waste water samples were classified as C3 or C4 during the four collecting periods, that is, at high or extremely high salinization risk. The different types of receiver soils of reject brine coming from such communities show meaningful alteration of their attributes and of their qualities throughout the periods, being that more noticeable during the drought periods and on the layers of soils with greater amount of clay, promoting different ratings for the same soil, being such ratings influenced directly by the waste water from desalination process
Keywords: Recursos hídricos; Solos salinos; Osmose reversa; Água residuária; Water resources; Saline soils; Reverse osmosis; Wastewater; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO::MANEJO E CONSERVACAO DO SOLO